Międzynarodowy Kongres Studiów Boecjańskich - Longosz, Stanisław (Vox Patrum, 1981)
Report from the International Congress of Boetian Studies, which took place in Pavia (Italy) on 5-8 October 1980 due to the 1500 anniversary of Boecius' birth.